Comparative analysis of features of the higher education system in Ukraine and France - Severyna, N. (НТУ "ХПИ", 2014)
Comparative analysis of the features of higher education of Ukraine and France provided the unification of European education in the framework of the Bologna process is carried out in the article. Features of formation of knowledge and skills at higher education institutions of the two countries were discussed. Differences and similarities regarding the organization of the learning process, the creation of educational and training environments in higher educational institutions of Ukraine and France have been described.

В статье проводится сравнительный анализ особенностей систем высших школ Украины и Франции при условии унификации европейского образования в рамках Болонского процесса. Рассмотрены особенности формирования знаний, умений и навыков в высших учебных заведениях двух стран. Описаны различия и общие черты относительно организации процесса обучения, создания воспитательной и образовательной сред в высших учебных заведениях Украины и Франции.
Сравнительный анализ особенностей систем высшего образования Украины и Франции
Keywords: Bologna process; professional training; European education; knowledge; skills; Болонский процесс; высшее образование; профессиональная подготовка